ANTIBAKTERI PADA PRODUK BIOTEKNOLOGI FARMASI BERUPA FORMULASI DAN SEDIAAN SABUN MANDI GEL KOMBUCHA BUAH NANAS MADU SUBANG - Fadilah, M. Fariz; Rezaldi, Firman; Kolo, Yuliana; Hidayanto, Fajar; Mubarok, Syariful (Sam Ratulangi University, 2023)
Kombucha from honey pineapple can be used as an active ingredient in formulations and preparations for shower gel as a pharmaceutical biotechnology product which has pharmacological activity in vitro in inhibiting the growth of Staphylococcus aureus, Staphylococcus epidermidis, Psedomonas aeruginosa, and Escherichia coli bacteria. This study aims to make formulations and preparations for shower gel with active ingredients from kombucha fermented pineapple madu subang solution which includes concentrations of 15%, 25% and 35%. This research method is laboratory experimental in nature where the first step is to make a shower gel base without the active ingredient as a negative control. The second step is to make a gel soap base with the active ingredient, kombucha fermented pineapple honey subang at concentrations of 15%, 25% and 35%. Providing widely available commercial body wash as a positive control. Disc diffusion is a popular method for testing the activity of an antibacterial. One way ANOVA and post hoc follow-up test are the parts used in the analysis of each shower gel formulation along with the two positive controls for the overall test bacteria. The results of this study proved that based on a P value <0.05 through a one way ANOVA test and continued through post hoc analysis, namely the formulation and preparation of kombucha shower gel, pineapple madu subang at a concentration of 35%, significantly different from 20% and 30% to the growth of the four test bacteria and 35% concentration of kombucha bath soap pineapple honey subang was the best treatment compared to the two controls and other treatments in inhibiting the growth of the four test bacteria.